The association between iron and vitamin D status in female elite athletes - Malczewska-Lenczowska, J.; Sitkowski, D.; Surala, O.; Orysiak, J.; Szczepanska, B.; Witek, K. (Nutrients, 2018)
Vitamin D may influence iron metabolism and erythropoiesis, whereas iron is essential for vitamin D synthesis. We examined whether vitamin D deficiencies (VDD) are associated with reduced iron status and whether progressive iron deficiency (ID) is accompanied by inferior vitamin D status. The study included 219 healthy female (14-34 years old) athletes. VDD was defined as a 25(OH)D concentration < 75 nmol/L. ID was classified based on ferritin, soluble transferrin receptor (sTfR), total iron binding capacity (TIBC) and blood morphology indices. The percentage of ID subjects was higher (32%) in the VDD group than in the 25(OH)D sufficient group (11%) (X2 = 10.6; p = 0.001). The percentage of VDD subjects was higher (75%) in the ID than in the normal iron status group (48%) (X2 = 15.6; p = 0.001). The odds ratios (ORs) for VDD increased from 1.75 (95% CI 1.02-2.99; p = 0.040) to 4.6 (95% CI 1.81-11.65; p = 0.001) with progressing iron deficiency. ID was dependent on VDD in both VDD groups (25(OH)D < 75 and < 50 nmol/L). The ID group had a lower 25(OH)D concentration (p = 0.000). The VDD group had lower ferritin (p = 0.043) and iron (p = 0.004) concentrations and higher values of TIBC (p = 0.016) and sTfR (p = 0.001). The current results confirm the association between vitamin D and iron status in female athletes, although it is difficult to assess exactly which of these nutrients exerts a stronger influence over the other